Teachers and Technology: Christian Education Teacher Strategies in Implementing Online-based Learning in Pandemic Times - Talizaro Tafonao; Benteng Martua Mahuraja Purba (Universitas Veteran Bangun Nusantara, 2021)
The purpose of this research is to investigate the efficacy of teacher-led online teaching practices during pandemics. In this digital era, all teachers are required to adapt quickly to technological developments. But in reality, some Christian Education teachers are still not ready to transform in utilizing the application of technology as described in this article. Based on that question, the authors reviewed this topic to explain the essential steps teachers should take in implementing online-based learning strategies during pandemics. A descriptive qualitative research method was adopted in this work. The researchers gathered information through reading academic articles and books. The author analyses the data through analytical techniques by reducing, classifying, and verifying the study of this article. The results obtained in this study are very effective if Christian Education teachers apply online-based learning strategies in a way that teachers learn to provide features that are easily accessible to students. Teachers learn to design learning online, and teachers get used to providing stimulus to learners. Thus, online learning requires every teacher to adapt, innovate, and utilize digital media to facilitate the learning process during the pandemic.